Strategi Pembelajaran Langsung - Anggi Ria Awalia; M. Shabir U; Usman U (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Learning strategy is an activity plan that uses methods and utilizes various resources in a learning process. Learning strategy is very important because the strategy is designed to achieve a certain goal. In delivering learning content, managing strategies and making decisions about delivering strategies must require the right strategy, in order to form a learning model that is in accordance with the conditions and circumstances of the school environment so that the methods, techniques and tactics that will be used can be in accordance with the procedures that we have designed at the beginning. This study is a literature review with a qualitative descriptive approach. The results of the study show that direct learning strategies are teacher-centered learning (teacher centered) therefore this learning implies direct interaction between teachers and students. Direct learning strategies are learning that is directly directed by teachers through specific tasks that must be completed by students under the direct supervision of teachers through the learning phase facilitated by the teacher.